1999
DOI: 10.1177/107155769900600502
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Fertility and Ovarian Function and Minimizing Chemotherapy-Induced Gonadotoxicity in Young Women

Abstract: BACKGROUND: After the improved long-term survival in young women with lymphoma and leukemia undergoing chemotherapy, the preservation offuturefertility has been thefocus of recent interest. AREAS OF REVIEW: Three major topics are reviewed. They include the following: (1) the role of chemotherapy in the treatment of malignant and nonmalignant disease in young women, the types ofchemotherapy and their gonadal effects (differing between ovaries and testes) in both human and other species, and the reasons for diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
89
0
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 90 publications
3
89
0
10
Order By: Relevance
“…Although some patients are currently able to preserve their fertility during cancer treatment by embryonic cryopreservation [3][4][5], ovaries remain in situ and exposed to chemotherapy drugs in nearly all patients. GnRH agents have been tested as ovarian protectants with mixed results [6][7][8][9][10]. An alternative conservative strategy to protect the ovary from cytotoxic therapy is needed to maintain not only oocyte quality but also hormone production for the support of follicle growth and pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Although some patients are currently able to preserve their fertility during cancer treatment by embryonic cryopreservation [3][4][5], ovaries remain in situ and exposed to chemotherapy drugs in nearly all patients. GnRH agents have been tested as ovarian protectants with mixed results [6][7][8][9][10]. An alternative conservative strategy to protect the ovary from cytotoxic therapy is needed to maintain not only oocyte quality but also hormone production for the support of follicle growth and pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary clinical trials have shown that the administration of gonadotropin-releasing hormone agonists (GnRH-a) to young women during the standard chemotherapy regimes resulted in resumption of ovarian function in a significant percentage of patients after termination of treatment (2,9,10). However, previous studies on the use of GnRH-a in association with chemotherapy in young patients with malignancies included heterogeneous groups of women with different diseases.…”
mentioning
confidence: 97%
“…This increase in survival is a result of the introduction of effective chemotherapy, such as when MOPP (mechlorethamine, vincristine, prednisone, and procarbazine) and/or ABVD (adriamycin, bleomycin, vinblastine, and decarbazine) and its variants are used (3). Although the cytotoxic effect of these treatments is reversible in tissues with rapidly dividing cells such as bone marrow, the gastrointestinal tract, and thymus (4), it appears to be progressive and irreversible in the ovary, in which germ cells are limited in number and cannot be regenerated (1,2,5).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Blumenfeld und Mitarbeiter sowie Howell und Recchia konnten in einigen Studien mit kurzem Follow-up durch Gabe von GnRH-Analoga vor und während der Chemotherapie bei jungen Frauen mit malignen Erkrankungen eine protektive Wirkung auf die Ovarialfunktion nachweisen [3,5,6,7,8,13,23]. Allerdings macht die retrospektive Analyse der Kontrollgruppe die Beobachtungen weniger aussagekräftig.…”
Section: Effektivität Der Gonadotropinsuppressionunclassified